Peran Komisi Pemilihan Umum dalam Penetapan Daftar Pemilih Tetap pada Pemilihan Kepala Daerah dan Wakil Kepala Daerah (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2025)
General elections play an important role in a democratic country like Indonesia, guaranteeing people's sovereignty, government legitimacy and people's sovereignty. regular change of power. The importance of the Permanent Voter List (DPT) lies in the ability of citizens to exercise their right to vote effectively. However, challenges often arise in compiling accurate voter lists, which are critical to the functioning of the democratic process. The General Election Commission (KPU) plays an important role in this process by determining eligible voters, coordinating data collection, and utilizing the Sidalih voter list information system. The KPU also collaborates with regional institutions, ensuring the accuracy of voter lists through cross-checking activities, and designating voting areas, all to maintain the integrity of the election and encourage citizen participation.